Analisis Sifat Mekanik dan Sifat Termal Komposit Poliuretan Berpenguat Serat Nanas Dan Cangkang Kemiri - Silvia Silvia; Rochmi Widjajanti; Ida Nur Apriani (Proklamasi 45 University, 2022)
The development of materials that have good durability continues to grow rapidly. One way to increase the durability of a material is the manufacture of composite materials. Composite is a material consisting of a matrix and a reinforcing material. The purpose of this study is first to determine the best composition for fillers and matrix in the manufacture of polyurethane composites reinforced with pineapple fiber and candlenut shells, second to determine the mechanical properties of the composite material, and third to determine the thermal stability of the composite material. To find out the best composition results, tensile strength tests were carried out using the Universal Testing Machine (UTM) and thermal properties were tested using Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA). In this study, variations in the composition of composite materials from polyurethane, pineapple fiber, candlenut shell powder and aluminum powder will be carried out with the percentages of filler and matrix of 50:50, 60:40 and 70:30 (%). Based on the results of the study, the composite with a variation of 50:50(%) has the best mechanical properties with a tensile strength 10,592 MPa, strain value (elongation at break) 0.7072% and modulus of elasticity (E) 5526,054 MPa. Stability termal of composite was found that the composition with the ratio of filler and matrix 60:40 (%) is the best composition based on the thermal properties. It has a melting temperature 287.4℃ and begins to decompose at temperature 292.65℃.